(untitled) (Journal of Research Updates in Polymer Science, 2014)
Polyurethane foams functionalized with Sulfonic acid groups have been found to be strong cation exchangers. This novel property of the foam was used to exchange lead (Pb2+) ions from aqueous solutions. Polyurethane foam synthesis is based on addition polymerization of the highly reactive isocyanate (-NCO) groups of an isocyanate with the hydroxyl (–OH) groups of a polyol to form the urethane species. Toluene-2,4-2,6- diisocyanate was reacted with Polypropylene glycol 1200 in 2:1 molar ratio to form a linear pre-polymer. The linear pre-polymer was further polymerized using a chain extender, N, N-bis (2-hydorxyethyl)-2-aminoethane-sulfonic acid (BES). BES also acts as a functional group to exchange Pb2+ ions. A set of experiments were designed to study various process parameters. The functionalized polyurethane foam was characterized by Fourier transform infrared spectroscopy, gel permeation chromatography, scanning electron microscopy, and energy dispersive x-ray spectroscopy. The Pb2+ ion exchange capacity was determined using an Inductively Coupled Plasma Mass Spectrometer. The maximum Pb2+ ion exchange capacity of the foam was found to be 47 parts per billion per gram (ppb/g) from a 100 parts per billion (ppb) Pb2+ solution over a period of 60 minutes. A multistage batch filtration process increased the Pb2+ ion removal to 50-54 ppb/3g of foam over a period of 90 minutes.